Implementation of the philosophical foundation of education with the concept of free learning by the Minister of Education Nadiem Makarim - Utami, Hidayati Puja (Jurnal Penelitian Pendidikan, 2020)
The writing of this article aims to describe the phenomenon linked to the concept of Merdeka Learning which was invented by the Minister of Education and Culture (Nadiem Makarim) which refers to the philosophical basis of education. Ideally, the Merdeka Belajar policy for its implementation to work well, it requires a philosophical foundation as well as its analysis. Education itself cannot be carried out on a regular basis, with clear orientations for its objectives, in relation to the content of the program, and effective and efficient methods or methods of implementation only if it is implemented in reference to a solid foundation. So that the objectives are clear, that the content of the program is correct and that the methods of implementation are efficient and effective.